A Study on Developing Autonomous Procurement System (APS) - Mazen A Al-Sinan; Zainab A Aljaroudi (International Journal of Supply Chain Management, 2022)
This paper provides a full disclosure of a pending patent that was filed with the United States Patent and Trademark Office (USPTO) in March 2020. The proposed patent provides an autonomous solution conducting a procurement process for services and materials. The paper also provides a brief description of a typical procurement process for services as a background.